Functionalization of Electrospun Nanofibers and Fiber Alignment Enhance Neural Stem Cell Proliferation and Neuronal Differentiation - Amores de Sousa, Miriam C.; Rodrigues, Carlos A. V.; Ferreira, Inês A. F.; Diogo, Maria Margarida; Linhardt, Robert J.; Cabral, Joaquim M. S.; Ferreira, Frederico Castelo (Frontiers in Bioengineering and Biotechnology, 2020)
Neural stem cells (NSC) have the potential to generate the cells of the nervous system and, when cultured on nanofiber scaffolds, constitute a promising approach for neural tissue engineering. In this work, the impact of combining nanofiber alignment with functionalization of the electrospun poly-ε-caprolactone (PCL) nanofibers with biological adhesion motifs on the culture of a NSC line (CGR8-NS) is evaluated. A five-rank scale for fiber density was introduced and a 4.5 level, corresponding to 70 - 80% fiber density, was selected for NSC in vitro culture. Aligned nanofibers directed NSC distribution and, especially in the presence of laminin (PCL-LN) and the RGD-containing peptide GRGDSP (PCL-RGD), promoted higher cell elongation, quantified by the eccentricity and axis ratio. In situ differentiation resulted in relatively higher percentage of cells expressing Tuj1 in PCL-LN as well as significantly longer neurite development (41.1 ± 1.0 μm) than PCL-RGD (32.0 ± 1.0 μm), pristine PCL (25.1 ± 1.2 µm) or PCL-RGD randomly oriented fibers (26.5 ± 1.4 μm), suggesting that the presence of LN enhances neuronal differentiation. This study demonstrates that aligned nanofibers, functionalized with RGD, perform as well as PCL-LN fibers in terms of cell adhesion and proliferation. The presence of the full LN protein improves neuronal differentiation outcomes, which may be important for the use of this system in tissue engineering applications.